Hereditary polyneuropathy in the Alaskan Malamute - Rentmeister, K.; Bilzer, T.; Petri, S.; Schanen, G.; Fehr, M.; Distl, O.; Tipold, A. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2012)
Objective: To prove the hypothesis that a polyneuropathy in Alaskan Malamutes has a genetic background. Material and methods: Pedigrees of 131 related Alaskan Malamutes were included in the current study. Neurological examination, electrodiagnosis as well as muscle and nerve biopsies could be performed in 10 dogs. Information about the disease status of the other 121 Alaskan Malamutes were supplied by referring veterinarians, breeders and owners. Segregation analysis using four different models (monogenic, polygenic, mixed monogenicpolygenic and the phenotypic model) was performed on 71 dogs to test the different mechanisms of genetic transmission. Results: In seven clinically affected dogs abnormal electromyographic findings and reduced nerve conduction velocity were detected. Suspected diagnosis of polyneuropathy was confirmed by nerve biopsy results, characterized by axonal degeneration and hypomyelination. Muscle specimens revealed signs of neurogenic myopathy. Three related clinically normal Alaskan Malamutes also displayed moderate neuromuscular changes in histopathology. In the segregation analysis the polygenic model proved as best suitable to explain the observed segregation pattern among all other models tested. Conclusion: The current study could demonstrate that polyneuropathy in Alaskan Malamutes is a hereditary disease with variable phenotypic expression ranging from severely affected to subclinical forms, which has to be considered in future gene analysis studies.
Keywords: Dog; electrodiagnosis; muscleand nerve biopsy; segregation analysis